1995
DOI: 10.1136/emj.12.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of knee sprains: modified Robert Jones or elastic support bandage?

Abstract: The aim of this investigation was to compare in a prospective randomized study the outcome of painful, traumatic knee injuries when treated with either the modified Robert Jones (MRJB) or elastic support bandage (ESB). Patients with moderate or severe unilateral knee injury presenting to our department within 24 h were randomized into two treatment groups receiving either the MRJB or an ESB. The main outcome parameters of the study were the amount of pain relief required, the speed of recovery, mobility and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…We found similar levels of pain and swelling in both groups in our study. The complications, including bruises and blisters [7], appeared to occur more in Group 1.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We found similar levels of pain and swelling in both groups in our study. The complications, including bruises and blisters [7], appeared to occur more in Group 1.…”
Section: Discussionmentioning
confidence: 97%
“…Based on the results, we could not conclude the advantages of reducing blood loss and transfused blood units in clinical practice. In a study comparing the advantage of the MRJB with the elastic support bandage in patients with knee sprains, Hughes et al [7] found no differences in the VAS for pain, ranges of motion, and analgesic consumption from the initial period to 3 weeks postoperative. However, they reported an elastic support bandage made the patients feel more comfortable than the MRJB during the first week in the early postinjury period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients with knee injuries are initially managed symptomatically using a variety of means such as a pressure bandage, a splint, crutches, and painkillers; then, after 4 days, they are reviewed in the general surgical outpatient clinic [7].…”
Section: Introductionmentioning
confidence: 99%